Methods for database ciphering - Maitham Ali Naji; Dalal Abdul Mohsin Hammood; Nuha Abdul Razik Al Debagh (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this paper Caesar and Vigenere methods have been used for table ciphering. Each record has unique and independent keys to the next record to get high security. The cipher text stored in script file that separates the content of fields by semicolon. The second part is the process of creating a new database using the Object called Data Access Object (DAO) and then create table and it is fields. The program gets plaintext of the table by applying the decryption rules of two methods.